Analisis Faktor Yang Mempengaruhi Minat Beli Mahasiswa Terhadap Pembelian Produk UMKM - Lucky Mahesa Yahya; Rahmi Datul Ulfa; Renada Amalia; Mutia Khairun Nisa (JURNAL RISET MANAJEMEN (JURMA), 2023)
The term Micro, Small and Medium Enterprises is called MSMEs. In its simplest form, MSMEs refer to all types of businesses, including those carried out by households, small business entities, organizations, and individuals. In order to improve the ability to create community independence, especially in the economic sector, Indonesia as a developing country makes MSMEs the main base of the community's economic sector. Purchasing decisions are steps by consumers to make judgments about whether or not to buy a product when making a purchase. This indicator explains what factors influence purchasing decisions, namely (1) buying stability after knowing consumer product information. (2) decide to buy because of the preferred brand (3) buy because of wants and needs (4) buy because of recommendations from others (5) buy because of price and quality. Quantitative research with a questionnaire which translates the diagram of the results of the questionnaire into the form of analysis with a sample of students with a sample of 30 respondents and is supported by secondary data in the form of competent previous research literature and related to the title discussed. Based on the results of the study, it can be concluded that the most influential factor in the decision to buy MSME products made by students is the purchase factor because it is in accordance with their wishes and needs.